Nasopharyngeal microbiome of COVID-19 patients revealed a distinct bacterial profile in deceased and recovered individuals. (December 2022) - Kumar, Dinesh; Pandit, Ramesh; Sharma, Sonal; Raval, Janvi; Patel, Zarna; Joshi, Madhvi; Joshi, Chaitanya G.
Abstract: The bacterial co-infections in SARS-CoV-2 patients remained the least explored subject of clinical manifestations that may also determine the disease severity. Nasopharyngeal microbial community structure within SARS-CoV-2 infected patients could reveal interesting microbiome dynamics that may influence the disease outcomes. Here, in this research study, we analyzed distinct nasopharyngeal microbiome profile in the deceased (n = 48) and recovered (n = 29) COVID-19 patients and compared it with control SARS-CoV-2 negative individuals (control) (n = 33). The nasal microbiome composition of the three groups varies significantly (PERMANOVA, p-value <0.001), where deceased patients showed higher species richness compared to the recovered and control groups. Pathogenic genera, including Corynebacterium (LDA score 5.51), Staphylococcus, Serratia, Klebsiella and their corresponding species were determined as biomarkers (p-value <0.05, LDA cutoff 4.0) in the deceased COVID-19 patients. Ochrobactrum (LDA score 5.79), and Burkholderia (LDA 5.29), were found in the recovered group which harbors ordinal bacteria (p-value <0.05, LDA-4.0) as biomarkers. Similarly, Pseudomonas (LDA score 6.19), and several healthy nasal cavity commensals including Veillonella, and Porphyromonas, were biomarkers for the control individuals. Healthy commensal bacteria may trigger the immune response and alter the viral infection susceptibility and thus, may play important role and possible recovery that needs to be further explored. This research finding provide vital information and have significant implications for understanding the microbial diversity of COVID-19 patients. However, additional studies are needed to address the microbiome-based therapeutics and diagnostics interventions. Graphical abstract: Image 1 Highlights: Nasopharyngeal microbiome analysis of the SARS-CoV-2 patients from Gujarat, India. Opportunistic pathogens and dysbiosis of microbiota revealed bacterial co-infections could drive clinical outcome and disease severity of patients. Identification and characterisation of bacterial communities among control, healthy, deceased COVID-19 patients. Healthy commensal bacteria may trigger the immune response and alter the viral infection susceptibility. Biomarker taxa determination using Linear Discriminant Analysis (LDA) Effect Size (LEfSe) analysis.